2008
DOI: 10.1088/0022-3727/41/8/085406
|View full text |Cite
|
Sign up to set email alerts
|

Changes in dielectric properties of Pb(In1/2Nb1/2)O3-PbTiO3ceramics under compressive stress applied parallel and perpendicular to an electric field

Abstract: The influences of compressive stress on the dielectric properties of (1 − x)Pb(In1/2Nb1/2)O3–xPbTiO3 (x = 0.1–0.5) ceramics was investigated in this study. The dielectric properties were measured under compressive stress applied parallel and perpendicular to electric field. The results clearly showed that the superimposed compression stress had pronounced effects on the dielectric properties of PIN–PT ceramics. In general, with increasing compressive stress the dielectric constant of the ceramics increased and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
3
3
0
Order By: Relevance
“…The changes in the dielectric loss tangent are, on the other hand, opposite to those of the parallel stress case. For the case of the compressive stress applied perpendicular to the direction of the electric field, only few previous experimental works have been carried out on some commercial hard and soft PZT ceramics, PIN-PT and PMN-PT ceramics [17,18,24,26,33,34]. Interestingly, the results observed in this present study are generally very similar to those obtained earlier in the Pb-based perovskite ceramics mentioned above.…”
Section: Tablesupporting
confidence: 88%
See 3 more Smart Citations
“…The changes in the dielectric loss tangent are, on the other hand, opposite to those of the parallel stress case. For the case of the compressive stress applied perpendicular to the direction of the electric field, only few previous experimental works have been carried out on some commercial hard and soft PZT ceramics, PIN-PT and PMN-PT ceramics [17,18,24,26,33,34]. Interestingly, the results observed in this present study are generally very similar to those obtained earlier in the Pb-based perovskite ceramics mentioned above.…”
Section: Tablesupporting
confidence: 88%
“…0.9PZT-0.1PZN, 0.8PZT-0.2PZN, and 0.7PZT-0.3PZN, is attributed to more available domain states in the compositions [6][7][8], hence much larger change is observed. Similar mechanism has been reported for other ferroelectric systems [19,25,26].…”
Section: Tablesupporting
confidence: 86%
See 2 more Smart Citations
“…Our recent investigation showed that the dielectric constant of PZT-PCN ceramics increased significantly with increasing compressive stress applied parallel to the electric field direction, while the dielectric loss tangent showed an opposing trend [23]. Recently, many investigations also reported changes in the electrical properties of ferroelectric ceramics under compressive stress applied perpendicularly to the electric field [16,18,[24][25][26][27][28]. Therefore, it is the aim of this study to examine the dielectric properties of PZT-PCN ceramics under such compressive stress.…”
Section: Introductionmentioning
confidence: 96%